Fatty liver disease and lifestyle in youngsters: diet, food intake frequency, exercise, sleep shortage and fashion. (28th September 2015) - Trovato, Francesca M.; Martines, Giuseppe Fabio; Brischetto, Daniela; Catalano, Daniela; Musumeci, Giuseppe; Trovato, Guglielmo M.
Abstract: Background & Aims: Fatty liver is associated with alcohol habits and/or overweight/obesity. We challenged several lifestyle features associated with fatty liver and, particularly, with non‐alcoholic fatty liver disease (NAFLD). Among them, sleep shortage as a result of nightlife habits and a preference for plus‐size fashion were assessed. The latter consists of fashionable plus‐sized clothing for actual individuals' size and reflects a frequent attitude of some social or age groups, conceivably indicating more global and widespread trend and behaviour. Methods: We studied a group of 708 non‐diabetic youngsters, 458 women and 250 men, 21.72 ± 3.71 years old (range 15–35 years), referred for minor digestive ailments for clinical assessment, ultrasound detection of fatty liver and nutritional counselling. Details of personal history regarding lifestyle, food intake frequency and alcohol intake, dietary and physical exercise profile, sleep duration and clothing preferences were recorded. Results: The prevalence of NAFLD in this cohort of youngsters is 67/708 (9.4%). Even if it is quantitatively very low in both groups, the average alcohol intake, always below 20 g/day, is greater in NAFLD subjects (5.83 ± 4.32 g) vs. subjects with normal liver (2.02 ± 3.20 g). The number of meals/day and adherence to a Mediterranean diet profile are smaller in NAFLD subjects. By multiple regression, BMI, sedentary life, plus‐sized clothing for their actual size, sleep shortage and lower frequency of daily food intake are associated with the presence of NAFLD. Conclusions: Onset and continuation of fatty liver disease, beyond food and exercise quantity and quality, with their effects on obesity, may also be associated with other aspects of lifestyle.